Calculation of welfare effects of road pricing on a large scale road network - Tampère, Chris; Stada, Jim; Immers, Ben (Technological and Economic Development of Economy, 2009)
After a brief review of the theoretical principles of road pricing this paper presents the results of a modelling exercise aimed at ascertaining the effects of road pricing on a large road network. For the study area we chose an important part of the road network of Belgium, situated in the corridor between the main cities of Brussels and Ghent. Simulations were carried out using an elastic static traffic assignment method. Special care was taken to use realistic parameters for resource costs, time costs, external environmental costs and tax rates. The reduction of traffic caused by the increased trip prices as well as the route changes induced by the tolls were taken into account. The main objective of tolling as considered in this paper is the maximisation of the social welfare gain but possible adverse effects of tolling on traffic streams are also investigated. The relative merits of cordon and corridor tolling schemes are discussed. A combination of these two tolling schemes appears to give the best results, both in terms of welfare gain and traffic streams.Kelių apmokestinimo didelio mastelio kelių tinkle socialinės gerovės efekto apskaičiavimasSantrauka. Po trumpos teorinės kelių apmokestinimo apžvalgos aprašomi kelių apmokestinimo didelio mastelio kelių tinkle efekto nustatymo rezultatai. Analizei atlikti buvo pasirinkta svarbi Belgijos kelių tinklo dalis ‐ koridorius tarp pagrindiniu Briuselio ir Gento miestų. Ypatingas dėmesys kreiptas į tai, kad buvo panaudoti realūs išteklių, išorines aplinkos sąnaudų ir mokesčių parametrai. Modeliuota pagal lankstųjį statinį eismo nustatymo metodą. Nustatyta, kad eismas sumažėjo padidėjus kelionių kainoms, įvedus rinkliava už kelius. Aprašomas rinkliavos poreikis socialinei gerovei ir galimas nepalankus poveikis. Aptariami santykiniai privalumai, užkardos ir koridoriaus rinkliavų schemos. Šių dviejų rinkliavų schemų derinys duoda geriausių rezultatų tiek socialinei gerovei, tiek eismo srautams.Reikšminiai žodžiai: kelių mokestis, užkardos mokestis, koridoriaus mokestis, lankstus pastovus priskyrimo metodas, kelių tankis.First published online: 21 Oct 2010